Individual differences in competent consumer choice: the role of cognitive reflection and numeracy skills - Graffeo, Michele; Polonio, Luca; Bonini, Nicolao (Frontiers in Psychology, 2015)
In this paper, we investigate whether cognitive reflection and numeracy skills affect the quality of the consumers’ decision-making process in a purchase decision context. In a first (field) experiment, an identical product was on sale in two shops with different initial prices and discounts. One of the two deals was better than the other and the consumers were asked to choose the best one and to describe which arithmetic operations they used to solve the problem; then they were asked to complete the numeracy scale (Lipkus et al., 2001). The choice procedures used by the consumers were classified as “complete decision approach” when all the arithmetic operations needed to solve the problem were computed, and as “partial decision approach” when only some operations were computed. A mediation model shows that higher numeracy is associated with use of the complete decision approach. In turn, this approach is positively associated with the quality of the purchase decision. Given that these findings highlight the importance of the decision processes, in a second (laboratory) experiment we used a supplementary method to study the type of information search used by the participants: eye-tracking. In this experiment the participants were presented with decision problems similar to those used in experiment 1 and they completed the Lipkus numeracy scale and the Cognitive Reflection Test (CRT), (Frederick, 2005). Participants with a high CRT score chose the best deal more frequently, and showed a more profound and detailed information search pattern compared to participants with a low CRT score. Overall, results indicate that higher levels of cognitive reflection and numeracy skills predict the use of a more thorough decision process (measured with two different techniques: retrospective verbal reports and eye movements). In both experiments the decision process is a crucial factor which greatly affects the quality of the purchase decision.